Detailed kinetics of Fischer Tropsch synthesis over Fe-Co bimetallic catalyst considering chain length dependent olefin desorption. (15th January 2019) - Sonal; Pant, Kamal K.; Upadhyayula, Sreedevi
Highlights: Kinetic study of FTS and WGS reactions was performed over Fe/Co/SiO2 catalyst. Alkyl and alkenyl mechanisms were employed to develop the rate models. Model based on chain length dependent α-olefin desorption was able to fit the experimental trends. The model was able to explain the deviation from ASF distribution. Abstract: The present study envisages comprehensive kinetic modeling of the Fischer-Tropsch synthesis (FTS) reaction and the water gas shift (WGS) reaction. A series of experiments were performed over a silica-supported bimetallic catalyst (Fe/Co/SiO2 where Fe/Co w/w ratio was = 0.5) in a continuous fixed bed reactor (T = 493–553 K, P = 1.0–3.0 MPa, H2 /CO = 0.5–2.5). The FTS process involves several reaction steps for hydrocarbons formation, thus a detailed mechanistic approach was employed for the kinetic modeling purpose. Langmuir–Hinshelwood–Hougen–Watson (LHHW) and Eley-Rideal (EL) approaches were used to derive the rate expressions for the reactions. The rate expressions were based on alkyl and alkenyl mechanisms wherein chain propagation and product desorption steps were considered as the rate-determining steps. Moreover, in the product desorption steps, two different approaches were implemented. The first one was based on α-olefin readsorption; whereas the second one utilized hydrocarbon chain length (carbon) dependent α-olefin desorption. Thus, eight different elementary reaction networks for hydrocarbon formation were used for model development. The models were fit and validated against the generated experimental data. The kinetic model based on carbon chain length dependent α-olefin desorption was able to predict the trends in experimental data successfully. Moreover, CO & H2 consumption rates, as well as the product formation rates from the experimental data, were in good agreement with the predicted values by the developed model. The activation energies for the formation of methane, paraffin, and olefins were calculated 70 kJ/mol, 113 kJ/mol, and 91 kJ/mol respectively using the developed model.